Transcriptomic analysis of Penaeus monodon in response to acute and chronic hypotonic stress - Ji, Jing; Wang, Qiaohuang; Li, Shuigen; Chen, Yanting; Zhang, Jiexin; Yu, Hanxiu; Xu, Jinzhen; Li, Miaomiao; Zheng, Renhao; Lin, Nan; Zhang, Ziping (Frontiers in Veterinary Science, 2024)
To investigate the different mechanisms of Penaeus monodon in response to acute and chronic hypotonic stress, RNA sequencing technology was employed to profile the gene expression patterns in the gill, hepatopancreas, and hemocyte at 0, 6, 48, and 72 hours post acute hypotonic stress treatment (with salinity immediately decreased from 20 psu to 4 psu) and at 0, 2, 10, 15 days during chronic hypotonic stress treatment (with salinity gradually decreased from 20 psu to 4 psu). The control group (SC) was maintained at a constant salinity of 20 psu. Differentially expressed genes (DEGs) were identified, followed by further validation using real-time quantitative reverse transcription PCR (RT-qPCR). A total of 34,217 genes were expressed through sequencing.Compared with the control group, 8503 DEGs were identified in the acute hypotonic stress group, comprising 3,266 up-regulated and 5,237 down-regulated genes. In the chronic hypotonic stress group, 8,900 DEGs were detected, including 3,019 up-regulated and 5,881 down-regulated genes.Gene Ontology (GO) functional annotation analysis indicated that DEGs were primarily enriched in biological processes such as cellular and metabolic processes, cellular components like membrane and other cellular components, and molecular functions including structural binding and catalytic activity. Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that DEGs were predominantly concentrated in five major pathways: metabolism, genetic information processing, environmental information processing, cellular processes, and biological systems. These pathways encompassed antigen processing and presentation, the NOD-like receptor signaling pathway, the Toll-like receptor signaling and cell apoptosis. The RT-qPCR validation of 11 DEGs (hsp70, hsp90, nlrp3, mincle, nlrp12, tlr4, myd88, imd, casp7, casp9 and toll) demonstrated that the trends observed in the quantitative results were consistent with those from the transcriptome analysis, thereby validating the reliability of transcriptome sequencing data. This study identified that hypotonic stress triggers physiological responses in P. monodon to both acute and chronic hypotonic conditions, offering valuable insights into the expression patterns of functional genes in the gills, hepatopancreas, and hemocytes of P. monodon under such stress. These findings provide foundational data and a theoretical basis for further research into the regulatory mechanism of P. monodon in response to hypotonic stress.